2020
DOI: 10.1002/jssc.202000520
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of three tropane alkaloids in goji berries by cleanup of the graphene/hexagonal boron nitride hybrids and ultra‐high‐performance liquid chromatography tandem mass spectrometry

Abstract: A modified quick, easy, cheap, effective, rugged and safe method was established for simultaneous determination of atropine, anisodamine, and scopolamine in goji berries by using ultra‐high‐performance liquid chromatography with tandem mass spectrometry. The graphene/hexagonal boron nitride hybrids were prepared and first applied as a cleanup adsorbent. Compared to classical cleanup adsorbent (C18), the graphene/hexagonal boron nitride hybrids as adsorbent had better extraction efficiency for the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Early research indicated the presence of scopolamine in L. chinense and L. halimifolium within the tribe Lycieae 61,62 . However, all subsequent studies focusing on the detection of HS within this tribe failed to uncover their presence in any species or sample 47,[63][64][65][66][67][68] . Consequently, we confirmed L. chinense as a representative of the non-HS-producing Lycieae via additional examination (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Early research indicated the presence of scopolamine in L. chinense and L. halimifolium within the tribe Lycieae 61,62 . However, all subsequent studies focusing on the detection of HS within this tribe failed to uncover their presence in any species or sample 47,[63][64][65][66][67][68] . Consequently, we confirmed L. chinense as a representative of the non-HS-producing Lycieae via additional examination (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao and Shi (2020) investigated 30 goji berry batches from different production areas in China and reported the presence of trace levels of atropine in 29 of the samples (below the Limit of Detection (<LOD-23.4 µg/kg d.w.). Scopolamine and anisodamine could not be detected in the samples (LOD 1.5 µg/kg d.w.) [ 45 ].…”
Section: Tas In Food In Europementioning
confidence: 99%